PENGARUH PELAYANAN, LOKASI DAN PRODUK TERHADAP KEPUASAN PENGUNJUNG (Studi Pada Urbane Coffee Roaster Banjarmasin) - Junaidi -; periyadi -; Noorlaily Maulida (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
The objectives to be achieved in this study are 1) To analyze and prove that service has a significant effect on visitor satisfaction (Study on Urbane Coffee Roaster Banjarmasin)? 2) To analyze and prove that location has a significant effect on visitor satisfaction (Study on Urbane Coffee Roaster Banjarmasin). 3) To analyze and prove the product has a significant effect on visitor satisfaction (Study on Urbane Coffee Roaster Banjarmasin). 4) To analyze and prove that service, location and product have a significant effect on visitor satisfaction (Study on Urbane Coffee Roaster Banjarmasin). This type of research is quantitative. The results of interviews with several customer employees who have high loyalty to Urbane Coffee Roaster Banjarmasin are students or young people who make this place a gathering place with a total of 35 loyal customers. Given that the population is not too large, this study uses saturated sampling or uses all elements/members of the population as the research sample, totaling 35 customers. Based on the results of the study, it can be concluded as follows: 1) Service partially affects the satisfaction of visitors to Urbane Coffee Roaster Banjarmasin, as evidenced by the probability value of sig t 0.024 < 0.05 or t count 2.367 > t table 2.021. 2) Location partially affects visitor satisfaction at Urbane Coffee Roaster Banjarmasin, as evidenced by the probability value of sig t 0.000 < 0.05 or t arithmetic 7.457 > t table 2.021. 3) The product partially affects the visitor satisfaction of Urbane Coffee Roaster Banjarmasin, as evidenced by the probability value of sig t 0.629 < 0.05 or t count 0.488 > t table 2.02. 4) Service, Location and Product simultaneously affect the satisfaction of visitors to Urbane Coffee Roaster Banjarmasin, as evidenced by the probability value sig f 0.000 < 0.05 or f count 19.312 > f table 2.63 Keywords: Service, Location, Product, Visitor Satisfaction